Estabilidade de hipersuperfícies tipo-espaço em folheações espaço-tempo - Ribeiro Júnior, Ernani de Sousa (2009)
Give a generalized M─n+1 = I xØ Fn Robertson-Walker spacetime whose warping function verifies a certain convexity condition, we classify strongly spacelike hypersurfaces with constant mean curvature. More precisely, we will show that given x : Mn → M─n+1 a closed, strongly stable spacelike hypersurfaces of M─n+1 with constant mean curvature H, if the warping function Ø satisfying Ø ≥ max {HØ', 0} along M, is either maximal or a spacelike slice Mto = {to} x F, for some to Є I.